A comparative study on treatment for recycling of waste lubricating oil / Huey Ling Tan ... [et al.] - Tan, Huey Ling; Azmi, Nurul Nadhirah Binti; Veny, Harumi; Lim, Ying Pei; Passarella, Rossi (Universiti Teknologi MARA, 2022)
In the present work, the recycling of waste lubricating oil by treatment was investigated using three types of acids such as nitric acid, hydrochloric acid, and sulphuric acid. This research aims to gain a high-quality refined lubricant oil using acid as an alternative to distillation process. The characteristics and quality of the treated lubricating oil were compared with the base oil by several parameters such as pour point, cloud point, dynamic viscosity, kinematic viscosity specific gravity and ash content, following American Society for Testing and Materials (ASTM) standards. Initially, filtration was employed to remove the dirt that may be present in the used lubricant oil, followed by adding gasoline to the used lubricating oil and centrifugation at 1500 rpm for 10 minutes. The atmospheric distillation was conducted for complete removal of water and gasoline. Finally, the lubricating oil was treated with the acids (nitric acid, hydrochloric acid, or sulphuric acid) and neutralised with 6% sodium hydroxide before being separated using settling and centrifugation. Results showed that sulphuric acid exceeds nitric acid and hydrochloric acid in treating the waste lubricating oil. Furthermore, treated waste lube oil using 20% sulphuric acid was comparable to the fresh lubricating oil. The results showed that the waste lube oil after acid treatment can be reused.